Distal Femoral Rotation Correlates With Proximal Tibial Joint Line Obliquity: A Consideration for Kinematic Total Knee Arthroplasty - Ng, Chung Kia; Chen, Jerry Yongqiang; Yeh, Jared Ze Yang; Ho, Jade Pei Yuik; Merican, Azhar Mahmood; Yeo, Seng Jin (Elsevier, 2018)
Background: We hypothesized that there is a correlation between the distal femoral rotation and proximal tibial joint line obliquity in nonarthritic knees. This has significance for kinematic knee arthroplasty, in which the target knee alignment desired approximates the knee before disease. Methods: Fifty computed tomography scans of nonarthritic knees were evaluated using three-dimensional image processing software. Four distal femoral rotational axes were determined in the axial plane: the transepicondylar axis (TEA), transcondylar axis (TCA), posterior condylar axis (PCA), and a line perpendicular to Whiteside's anterior-posterior axis. Then, angles were measured relative to the TEA. Tibial joint line obliquity was measured as the angle between the proximal tibial plane and a line perpendicular to the axis of the tibia. Results: There was a strong positive correlation between PCA-TEA and tibial joint line obliquity (r = 0.68, P <.001) as well as TCA-TEA and tibial joint line obliquity (r = 0.69, P <.001). In addition, the tibial joint line obliquity and TCA-TEA angles were similar, 3.7° ± 2.2° (mean ± standard deviation) and 3.5° ± 1.7° respectively (mean difference, 0.2° ± 0.2°; P =.369). Conclusion: Both PCA-TEA and TCA-TEA strongly correlated with proximal tibial joint line obliquity indicating a relationship between distal femoral rotational geometry and proximal tibial inclination. These findings could imply that the native knee in flexion attempts to balance the collateral ligaments toward a rectangular flexion space. A higher tibial varus inclination is matched with a more internally rotated distal femur relative to the TEA.